Valoración de las actividades antropogénicas sobre los varamientos de las tortugas marinas en la playa de Canoa – Manabí - Palacios Vélez, Jesús Gabriel (2019)
Sea turtles are important in the structure and dynamics of marine-coastal and oceanic ecosystems. Due to its function as a predator and therefore natural regulators of certain species, and indicators of the health of the coastal and marine environments of the beaches. The general objective of this research was to evaluate the anthropogenic activities on the strands of sea turtles on the beach of Canoa - Manabí. For this, an inventory was carried out and characterized the anthropogenic tensors and threats as a baseline to establish their potential impact on the sea turtle stranding. Surveys and interviews were conducted with local fishermen, tourists and hotel managers, local restaurants. Four linear transects of approx. 3 km above the coast, identifying and inventorying tensions and anthropic threats. As a result, 19 categories of tensioners and threats were determined, of which 13 are of permanent occurrence, evidencing the vulnerability of the species. Strandings were located and georeferenced along the transects of Chelonia mydas, Lepidochelys olivacea and Eretmochelys imbricata. Surveys and interviews revealed little knowledge of the local population regarding the ecological importance of turtles. Strandings were mainly attributed to 4 of the 19 tensors identified and of which the bycatch was the main one. For fishermen, turtles are considered a pest. An environmental education plan is planned to raise awareness of the problem and enhance the ecological importance of sea turtles in the community of Canoa.